THE EXTRACTIVE INDUSTRIES TRANSPARENCY INITIATIVE (EITI) AND SUSTAINABLE DEVELOPMENT - Dosmaganbetov, Ablay (Graduate School of Public Policy, 2021)
The Ph.D. Thesis considers the relationship between the EITI and sustainable development such as good governance, investment climate, and socio-economic development linkages in resource-rich developing economies. Generally, the EITI primarily aims to improve the transparency and accountability of revenue streams from extractive industries and their efficient use for public benefit. There are mixed findings between the EITI and governance quality that do not directly capture extractive industries' governance. Concerning the EITI and FDI/economic growth nexus, the scope of research is substantially restricted. A few studies conclude that EITI membership has a positive and negative impact on inward FDI and economic welfare, respectively. It is essential to mention that the mixed and bounded research findings do not give a possibility to identify the evident positive or negative influence of the EITI membership on sustainable development of both institutional/governance quality and business/investment climate. Thus, Ph.D. Thesis aims to find alternative measures for good governance that provide a better understanding of the role of the EITI for natural resources governance, FDI inflows, and socio-economic well-being. Apart from these objectives, several EITI country case studies on Azerbaijan and Kazakhstan's examples are considered to identify the importance of the EITI for regional settings. This work considers empirical analysis based on different quantitative research methods such as linear regression, state-, state with time-fixed effects panel regressions, dynamic panel regression, and interrupted time-series analysis. The diverse range of statistical approaches allows conducting comprehensive empirical analysis and overcoming several endogeneity issues such as unobserved heterogeneity, misspecification, and reverse causality (or problem of simultaneity). The key findings suggest that EITI is considered an effective tool to attract FDI, boost economic growth, improve government efficiency and quality of regulations in EITI-implementing countries. However, the EITI membership has no impact on other sustainability pillars such as corruption, internal investments, poverty alleviation, and legal frameworks. Furthermore, Azerbaijan and Kazakhstan cases provided findings that differ from the entire sample of resource-rich developing economies.
Keywords: Type of access: Embargo; accountability; development; extractive industries; governance; transparency